Republication: Two Premature Neonates of Congenital Syphilis with Severe Clinical Manifestations - Akahira-Azuma, Moe (Trop Med Health, 2015)
Congenital syphilis (CS) is a public health burden in both developing and developed countries. We report two cases of CS in premature neonates with severe clinical manifestations; Patient 1 (gestational age 31 weeks, birth weight 1423 g) had disseminated idiopathic coagulation (DIC) while Patient 2 (gestational age 34 weeks and 6 days, birth weight 2299 g) had refractory syphilitic meningitis. Their mothers were single and had neither received antenatal care nor undergone syphilis screening. Both neonates were delivered via an emergency cesarean section and had birth asphyxia and transient tachypnea of newborn. Physical examination revealed massive hepatosplenomegaly. Laboratory testing of maternal and neonatal blood showed increased rapid plasma reagin (RPR) titer and positive Treponema pallidum hemagglutination assay. Diagnosis of CS was further supported by a positive IgM fluorescent treponemal antibody absorption test and large amounts of T. pallidum spirochetes detected in the placenta. Each neonate was initially treated with ampicillin and cefotaxime for early bacterial sepsis/meningitis that coexisted with CS. Patient 1 received fresh frozen plasma and antithrombin III to treat DIC. Patient 2 experienced a relapse of CS during initial antibiotic treatment, necessitating parenteral penicillin G. Treatment was effective in both neonates, as shown by reductions in RPR. Monitoring of growth and neurological development through to age 4 showed no evidence of apparent delay or complications. Without adequate antenatal care and maternal screening tests for infection, CS is difficult for non-specialists to diagnose at birth, because the clinical manifestations are similar to those of neonatal sepsis and meningitis. Ampicillin was insufficient for treating CS and penicillin G was necessary.